To be a slave eaudiobook - Lester, Julius (Recorded Books Inc., 1995)
To Be a Slave stands apart from other historical accounts of slavery in one extraordinary way: it is told by the slaves themselves. Their stories will tell you what it felt like to be a slave in the United States-to wear shackles on your ankles, to feel whips lashing your back, and to work under the cruelest conditions. From African villages to Georgian auction blocks, from plantation fields to abolitionist hideaways, To Be a Slave brings one of the most painful chapters in American history to life for today's young people. Julius Lester skillfully weaves together the testimonies of slaves with his own clear-eyed commentary to create a powerfully moving, unflinchingly honest view of black life in the old South. A Newbery Honor Book, a New York Times Outstanding Book of the Year, and a School Library Journal Best Book of the Year, To Be a Slave is an extraordinary lesson in history and humanity that no young person will forget.